KUALITAS NUTRISI ANEKA TEPUNG DAN KUE TALAM BERBASIS BAHAN PANGAN PULAU ENGGANO DENGAN PENAMBAHAN Lactobacillus plantarum B110 - Tatik Khusniati; Sulistiani Sulistiani; Abdul Choliq; Dhea Loka Nanta; Dita Kusuma Wardani; Dahniar Saraswati (BERITA BIOLOGI, 2016)
Nine foodstuffs from Enggano island were processed to flour as wheat flour alternative. To increase flour quality and its derivative product, Lactobacillus-plantarum B110 was added those flour and talam cake made from such flour. They were forest cassava (Dioscorea sp.), ararut sago (Marantha arundinacea), tacca (Tacca Leontopetaloides), egg taro (Alocasia sp.), oil taro (Alocasia sp.), gadung (Dioscorea hispida), gogo rice (Oryza sativa), corn (Zea mays), and belinjo (Gnetum gnemon).  The quality assessment consisted of HCN detection (qualitative), nutrition contents (proximate analysis), acid  (titration method), glucose (GOD-POD kit), and organoleptic tests (20 panelists). The results show that acid and glucose contents of the nine flours increased after L. plantarum B110 addition. Acid content of  the flours was 0.0144-0.2475%, while  glucose was  0.056-0.449%.  Carbohydrate, energy and acid contents of L. plantarum B110 talam cake were higher than control, which those were 34.13%, 190.33 cal/100gr, 0.00082%, while protein, lipid, water, ash were 1.75%, 5.22%, 57.9 %, 1.01%, respectively. The talam cake was accepted by panelists with values: 5.50 (taste), 5.6 (colour), 4.55 (flavour), 4.00 (texture), 4.35 (homogeneous). It was concluded that the flour and talam cake quality increased with addition of L. plantarum B110.